2018
DOI: 10.1177/0333102418788347
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of erenumab (AMG334) in chronic migraine patients with prior preventive treatment failure: A subgroup analysis of a randomized, double-blind, placebo-controlled study

Abstract: Background Erenumab was effective and well tolerated in a pivotal clinical trial of chronic migraine. Here, we evaluated efficacy and safety of monthly erenumab (70 mg or 140 mg) versus placebo in the subgroup of patients who had previously failed preventive treatment(s) (≥ 1, ≥ 2 prior failed medication categories) and in patients who had never failed. Methods Subgroup analyses evaluated change from baseline in monthly migraine days; achievement of ≥ 50% and ≥ 75% reduction in monthly migraine days; and chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 12 publications
13
128
0
4
Order By: Relevance
“…Preliminary findings in erenumab‐treated patients (140 mg dose) with episodic migraine who had failed at least one previous preventive drug class demonstrated greater placebo‐adjusted treatment differences in the treatment failure subgroups versus the overall population . Similar findings were observed, with greater clinical benefits observed for the erenumab 140 mg dose amongst patients with chronic migraine after monthly erenumab injections versus placebo in patients with prior treatment failures (≥1, ≥2 and ≥3) .…”
Section: Discussionsupporting
confidence: 77%
“…Preliminary findings in erenumab‐treated patients (140 mg dose) with episodic migraine who had failed at least one previous preventive drug class demonstrated greater placebo‐adjusted treatment differences in the treatment failure subgroups versus the overall population . Similar findings were observed, with greater clinical benefits observed for the erenumab 140 mg dose amongst patients with chronic migraine after monthly erenumab injections versus placebo in patients with prior treatment failures (≥1, ≥2 and ≥3) .…”
Section: Discussionsupporting
confidence: 77%
“…Significantly more erenumab, than placebo‐treated subjects, achieved ≥50% reduction in MMD (30% vs 14%). In CM subjects who failed 0 vs >1 preventive (n = 214 vs 327) erenumab achieved a change in MMD of 6.1 vs 7.0 (140 mg), 7.9 vs 5.4 (70 mg) and 5.7 vs 2.7 (placebo) days . A higher erenumab dosage seemed to work better in CM subjects who have failed previous preventives.…”
Section: Cgrp Function‐blocking Therapy In Migraine and Cluster Headachementioning
confidence: 93%
“…This report suggested that erenumab 140 mg might have additional benefit compared with 70 mg. The ≥50% reduction in mean monthly migraine days was reported in 41.3% of those with ≥2 previous prevention trials in the 140‐mg group, 35.6% in the 70‐mg group, and 14.2% of the placebo group …”
Section: Other Erenumab Trials and Analysesmentioning
confidence: 94%